Challenges Associated with Cross-Jurisdictional Analyses using Administrative Health Data and Primary Care Electronic Medical Records in Canada. (2018) - Katz, Alan; Enns, Jennifer; Wong, Sabrina T; Williamson, Tyler; Singer, Alexander; McGrail, Kimberlyn; Bakal, Jeffery A; Taylor, Carole; Peterson, Sandra
No abstract available